2005
DOI: 10.1128/aem.71.12.8738-8743.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of Extraradicular Biofilm-Forming Bacteria Associated with Refractory Endodontic Pathogens

Abstract: Bacterial biofilms have been found to develop on root surfaces outside the apical foramen and be associated with refractory periapical periodontitis. However, it is unknown which bacterial species form extraradicular biofilms. The present study aimed to investigate the identity and localization of bacteria in human extraradicular biofilms. Twenty extraradicular biofilms, used to identify bacteria using a PCR-based 16S rRNA gene assay, and seven root-tips, used to observe immunohistochemical localization of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 31 publications
2
82
1
4
Order By: Relevance
“…For example, Noguchi et al have identified 113 biofilmforming bacterial species on root surfaces outside the apical foramen and associated with refractory periapical periodontitis [12]. More often, the denaturing gradient gel electrophoresis (DGGE) method is employed to separate PCR-amplified community 16S rRNA on the basis of G+C content [13].…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…For example, Noguchi et al have identified 113 biofilmforming bacterial species on root surfaces outside the apical foramen and associated with refractory periapical periodontitis [12]. More often, the denaturing gradient gel electrophoresis (DGGE) method is employed to separate PCR-amplified community 16S rRNA on the basis of G+C content [13].…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…However, NaOCl has cytotoxic and neurotoxic effects when extruded into periapical tissues (3). Although NaOCl acts directly on target bacteria, several factors-such as the anatomical complexities of root canals, deep invasion of microorganisms into dentinal tubules, and formation of biofilm on the surface of the root apex-make it difficult to completely eliminate microorganisms from root canals and periapical lesions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…P. gingivalis is also frequently detected from extraradicular biofilms, which are refractory infectious lesions that are located outside the root apex (31). The virulence factors of P. gingivalis, such as proteolytic activity, fimbriae, capsules, and hemagglutinating activity, have been described (29).…”
mentioning
confidence: 99%